2010
DOI: 10.1103/physrevc.82.054602
|View full text |Cite
|
Sign up to set email alerts
|

Power law behavior of the isotope yield distributions in the multifragmentation regime of heavy ion reactions

Abstract: Isotope yields have been analyzed within the framework of a Modified Fisher Model to study the power law yield distribution of isotopes in the multifragmentation regime. Using the ratio of the mass dependent symmetry energy coefficient relative to the temperature, asym/T , extracted in previous work and that of the pairing term, ap/T , extracted from this work, and assuming that both reflect secondary decay processes, the experimentally observed isotope yields have been corrected for these effects. For a given… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…The size of the fragmenting source is evaluated from the NN source multiplicities of all particles, determined by a moving source fit described in Ref. [34,44]. The excitation energy of the fragmenting system is chosen to give an average value roughly similar to those of the experiment.…”
Section: Excitation Energy and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The size of the fragmenting source is evaluated from the NN source multiplicities of all particles, determined by a moving source fit described in Ref. [34,44]. The excitation energy of the fragmenting system is chosen to give an average value roughly similar to those of the experiment.…”
Section: Excitation Energy and Discussionmentioning
confidence: 99%
“…As discussed in detail in Ref. [34], the events measured by this IMF trigger belong essentially to the event class of semicentral collisions. The telescope consisted of four Si detectors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) was applied to the cold fragments in Ref. [41], they showed that useful information can be extracted to elucidate the effects of the secondary decay process. In that case, T and other parameters do not correspond to those in the primary hot nuclear matter but do correspond to those modified by the secondary decay process.…”
Section: Isobaric Yield Ratio Methodsmentioning
confidence: 99%
“…Based on the isobaric yield ratio (IYR), the IBD method provides cancellation of both the system dependence parameters [8][9][10][11], the free energies of isobars [3], and the terms contributing to the free energy of fragments [8,[12][13][14][15][16] in the formula determining the cross sections of fragment. The target dependence of IBD has been studied by investigating the measured fragments in 140A MeV 40,48 Ca and 58,64 Ni projectile fragmentation reactions on the 9 Be and 181 Ta targets [17], which have been performed by Mocko et al at the National Superconducting Cyclotron Laboratory (NSCL) in Michigan State University [18].…”
Section: Introductionmentioning
confidence: 99%